ANALISIS PENGGUNAAN MEDIA SOSIAL DALAM PEREKRUTAN PESERTA DIDIDK BARU DI SMP PLUS DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI - Muhammad Nasih; Abdul Hamid Ghozaly (Institut Agama Islam Darussalam Blokagung, 2021)
This study aims to: (1) find out the social media used in recruiting new students;(2) Knowing the Contribution of Social Media Used in Recruiting New Students; (3) Knowing the Strategy of Using Social Media in Recruiting New Students; (4) Knowing the Process of Recruiting New Students. In this study,researchers used qualitative methods using descriptive research.The researchers collected data using the methods of observation, interviews, and documentation and the analysis used the methods of data reduction, data presentation, and drawing conclusions.The results of this study: (1) Social Media Used in Recruiting New Students include: website, facebook, Instagram, youtube, whatsapp and other social networks. (2) Contribution of social media used in recruiting new students include: (a) Facilitating the process of recruiting new students; (b) Increasing prospective students; (c) Assist in the development of the school's vision. (3) Strategies for Recruiting New Students include: (a) Maximizing the use of social media; (b). Do promotions. (4) The process of recruiting new students includes (a) Formation of a new student admissions committee; (b) Meeting to determine new students; (c) Making announcements for new students; (d) Registration of new students; (e) Selection of new students; (f) Determination of accepted participants. Looking at the supporting and inhibiting factors from the research findings on the use of social media in recruiting students at SMP Plus Darussalam: There is a need for special personnel and innovation in the use of social media such as in the strategy of recruiting new students.